An Extended Mathematical Model For SIV To HIV From Chimpanzees To Human - Sule, Amiru (2017)
The purpose of this study is to investigate the transmission dynamics of SIV=HIV in humans, in the presence of chimpanzees that harbor Simian Immunodeficiency Virus (SIV) and to suggest some control strategies in sub-Saharan Africa. SIV was believed by some scientists to have ignited the emergence of HIV. This could be one of the reasons that make the disease endemic in sub-Saharan Africa where these chimpanzees are predominantly found. A basic model that consists of human and chimpanzee populations were formulated and the equilibrium points were determined. It was obtained that the disease free equilibrium point is locally asymptotically stable when the basic reproduction number is found to be less than unity and unstable otherwise.